Vitamin D and autoimmunity - Azrielant, Shir (Henry Stewart Talks, 2018)
Introduction to heliotherapy, Vitamin D sources and metabolism, Vitamin D deficiency and its epidemiology, Vitamin D and SLE, Vitamin D and type 1 diabetes, Vitamin D and MS, Vitamin D and rheumatoid arthritis, Vitamin D and other autoimmune diseases, Vitamin D supplementation, Vitamin D toxicity